2005
DOI: 10.1002/pen.20345
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of an epoxy-amine system at a high microwave frequency

Abstract: The dielectric properties of a curing diglycidyl ether of bisphenol A (DGEBA)/Jeffamine D-230 system have been studied over the temperature range of 20 -90°C at 2.45 GHz. It was found that, generally, both the dielectric constant and the dielectric loss factor of the system increased with temperature and decreased as the reaction proceeded. The epoxy resins at different extents of cure exhibited the ␥ relaxation, which can be described by the Arrhenius Rate Law. The relaxation is attributed to the motions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…On the basis of such studies, it is possible to assign certain molecular motions to each of the secondary relaxations in these epoxy systems. For example, the strength of the γ-relaxation decreases with cure [ 34 , 48 ], and it is not observed in the fully cured system [ 31 ], and thus it is generally agreed that the γ-relaxation in the pure epoxy and in the epoxy-amine system is related with the dynamics of dipoles localized in the epoxide end groups [ 30 ], or more generally with the local motions of dipoles of unreacted species [ 34 ]. As regards the β-relaxation, the early studies of Ochi and co-workers [ 49 ] by dynamic mechanical analysis (DMA) of anhydride cured epoxy systems showed that it was affected by the chemical structure of the curing agents but not by that of the epoxy resins, and subsequently from combined dielectric analysis (DEA) and DMA they assigned the β-relaxation to the formation of H-bonds between hydroxyl ether groups and methoxy branches [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of such studies, it is possible to assign certain molecular motions to each of the secondary relaxations in these epoxy systems. For example, the strength of the γ-relaxation decreases with cure [ 34 , 48 ], and it is not observed in the fully cured system [ 31 ], and thus it is generally agreed that the γ-relaxation in the pure epoxy and in the epoxy-amine system is related with the dynamics of dipoles localized in the epoxide end groups [ 30 ], or more generally with the local motions of dipoles of unreacted species [ 34 ]. As regards the β-relaxation, the early studies of Ochi and co-workers [ 49 ] by dynamic mechanical analysis (DMA) of anhydride cured epoxy systems showed that it was affected by the chemical structure of the curing agents but not by that of the epoxy resins, and subsequently from combined dielectric analysis (DEA) and DMA they assigned the β-relaxation to the formation of H-bonds between hydroxyl ether groups and methoxy branches [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the crosslinked epoxy networks, the polarizability and mobility of the un-reacted residual dipoles and newly produced dipoles may account for the relaxational dielectric loss. [13][14][15][16] Therefore the epoxy/ anhydride ratio should be stoichiometrically controlled; otherwise, excess epoxy or anhydride dipoles would exist in the crosslinked networks exerting double effect on dielectric loss. The first is that the excess epoxy or anhydride cause a ''looser'' network structure in which the dipoles or polar segments can rotate more easily along the electric field and the second is that the polarizability of excess epoxy or anhydride dipoles are higher than that of the polar segments in the crosslinking epoxy network.…”
Section: Dielectric Performancesmentioning
confidence: 99%
“…Material parameters are provided in Table II. The permittivity and loss tangent are approximated from [35]. The thermal properties of the composite have been measured using a Hot Disk TPS 2500 S, using standard techniques.…”
Section: B Multiphysics Modelingmentioning
confidence: 99%